Metaphor of ‘Adaptation’: a metaphoric rhetorical criticism on Aminuddin Baki’s Torch Movement Speech 3 - Halem Shah, Dil Froz Jan Sayed; Ahmad, Abdul Mua’ti Zamri; Hassan, Hamisah Zaharah; Shamshudeen, Rosya Izyanie; Ibrahim, Faridah (2017)
This paper looks at the Aminuddin Baki’s Torch Movement Speech 3 (Ceramah Gerakan Obor 3). It’s is to identify the type of metaphors used and how the metaphors are conveyed in the Torch Movement Speech 3 on ‘Adaptation’ of the Malays.The study hopes to identify the direction of the ‘Adaptation’ metaphor which is liken banana tree and its off springs.Many studies have been carried out on the biographical portion of Aminuddin Baki but none on all his Torch Movement Speeches that he had made on the progression and development of the Malays. A qualitative method was used through a rhetorical analysis.A Neo-Aristotelian Criticism is used in the analysis of speech of which this study demonstrates the relevance in the application of ancient Malay metaphors in the modern day communication interaction among the Malays.